ВНЕСОК У РОЗВИТОК ХУДОЖНЬОЇ ОСВІТИ МИТЦІВ ГАЛИЧИНИ (Педагогіка вищої та середньої школи, 2022)
The importance of art and pedagogical in heritage of Halychyna for the development and reform of modem art school in Ukraine has been analyzed of the author.
Keywords: художня освіта; художник-педагог; художник; національне мистецтво; авторська мистецька школа; учбова програма